Inoculacion transtraqueal de Pasteurella multocida tipo A en ratones - Fuentes, E.D.=700 1 Alvarez, E.; Fuentes, O.
(En, Es)
Ilus., 12 ref.
Keywords: PASTEURELLA MULTOCIDA; BACTERIA; INOCULACION; RATON; CUBA; INOCULACION TRANSTRAQUEAL TIPO A